Signed photograph of Edward R. Murrow (Tufts Archival Research Center, 2005)
7x9. Photo undated, approximate. Murrow's signature appears in green on the left-hand side of this photograph. A duplicate of MS025.002.045.00258.00014 (unsigned). Negative: MS025.002.045.00261b.00010.